Preclinical safety assessment and mutagenicity of the hydroethanolic extract of Syzygium campanulatum leaves. - Elham Farsi,; Kameh Esmailli,; Armaghan Shafaei,; Mohamed B Khadeer Ahamed,; Aman Shah Abdul Majid,; Munavvar Zubaid Abdul Sattar,; Amin Malik Shah Abdul Majid, (International Journal of Phytomedicine, 2016)
Syzygium campanulatum (Myrtaceae) is a species indigenous to Southeast Asia, a widely consumed medicinal herb and rich in phytochemical content and notable antiangiogenic and anti-colon cancer. Safety reports of administration of S. campanulatum are however lacking. In this study, we investigated the quality of dried leaves, chemical composition analyzed by FTIR and HPLC, phytochemicals content and repeated doses toxicity and mutagenicity effect of the hydroethanolic extract of S. campanulatum leaves (HESCL). The rats were divided into experimental and control groups and fed with 500, 1000, 2000 mg/kg/day of the hydroethanolic extract of S. campanulatum leaves for 28 and 90 days and with a single dose of 5000 mg/kg in acute study. The obtained results showed the dry leaves of S. campanulatum were devoid of any heavy metal and microbial contamination. The major components of HESCL were, respectively betulinic acid (60.43 mg/g.), total glycol saponins, total phenolics, total proteins, total tannins, and total flavonoids. No mutagenicity was detected in S. typhimurium auxotroph and no signs of clinical toxicity and mortality were observed in the experimental groups after 28 and 90-day experiment. However, significant (p < 0.05) statistical deviations were observed in hematological, and biochemical parameters but they were within the normal clinical range for rat, therefore not considered treatment-related. Based on these findings the fifty percent lethal dose was > 5000 mg/kg and the NOAEL was up to 2000 mg/kg for 90 days, as such HESCL is a relatively safe herb.